Strategy for Developing the Event and MICE (Meeting, Incentive, Convention, Exhibition) Industry in Bandar Lampung - Siregar, Damara Saputra; Sari, Desmala; Latifah Rizkiliana, Tina Nurzachra; Utami, Helidatasa (Journal of Event, Travel and Tour Management, 2024)
The Event and MICE (Meeting, Incentive, Convention, Exhibition) industry has become increasingly important in the global economy. Bandar Lampung, as one of Indonesia's developing cities, has significant potential to develop this industry. However, the development of the event and MICE industry in this city remains underexplored and not fully optimized. Data from the Ministry of Tourism and Creative Economy in 2023 indicates that Lampung is not yet among the top 10 event and MICE destinations in Indonesia. The Lampung MICE Forum 2022, held at Polinela, concluded that the development of the event and MICE industry in Bandar Lampung requires the formulation of a development strategy that is academically reviewed to be more systematic and targeted. This research aims to identify the factors affecting the development of the event and MICE industry in Bandar Lampung, identify gaps between ideal and actual conditions affecting this industry, and develop a strategy model for the industry. The research uses both primary and secondary data. Primary data is obtained through observation and interviews, while secondary data comes from literature reviews including books, journals, and policy documents. The research employs qualitative descriptive analysis, gap analysis, and spider chart analysis methods. The results indicate that developing the MICE industry in Bandar Lampung requires strategies such as enhancing human resources for MICE, improving MICE facilities, increasing public awareness of tourism development in Bandar Lampung, supporting MICE-related policies, and strengthening Bandar Lampung's branding as a MICE (Convention City) and Heritage City. Keywords: Development Strategy, Event Industry, MICE, Convention City